Understanding Venenata Dermatitis and its Toxin: Case Report - Godianto, Felicia; Suhardi, Silvi (Universitas Pahlawan Tuanku Tambusai, 2024)
Dermatitis venenata refers to a skin irritation reaction resulting from bites or direct contact between the skin and the saliva or hair of insects. This contact manifests as distinctive red patches on the skin, which may extend to surrounding areas and develop into painful blistering lesions. These lesions often exhibit a spreading pattern in areas of contact, commonly known as